A clinical evaluation of gelastic and dacrystic seizures: a multicenter study - Demir, Aylin Bican; Öz, Başak Yılmaz; Yıldız, Mustafa Onur; Türk, Bengi Gül; Tanrıverdi, Taner; Bekar, Ahmet; Yeni, Naz; Bora, İbrahim (Arquivos de Neuro-Psiquiatria, 2022)
Background Gelastic seizures are extremely rare, short-lasting, unprovoked, and uncontrollable laughing attacks. We conducted this retrospective evaluation to determine whether these symptoms, manifesting in different forms, such as cheerful laughter, laughing, smiling, and sobbing had any value in terms of etiology or localization.Methods A total of 31 patients who exhibited bouts of laughing or crying and who were under follow-up between 2000 and 2019 at tertiary epilepsy centers were included in the study. Laughing seizures were divided into three groups in terms of semiology (i.e., laughter with mirth, laughter without mirth, and smile). Dacrystic seizures were accompanied by some gelastic seizures and were divided into two groups in terms of semiology (i.e., weeping loudly [motor and voice-sobbing] and crying).Results Of the 27 patients with laughing seizures, 12 had seizures that manifested with smiling, 7 had seizures that manifested with laughing and mirth, and 8 had seizures that manifested with laughter without mirth. Dacrystic-gelastic seizures were observed in four patients, among whom 2 patients had crying and laughter without mirth and 2 patients had weeping loudly and laughter without mirth episodes.Conclusion Gelastic and dacrystic seizures often suggest hypothalamic hamartomas, in the literature. This rare ictal behavior can originate from different cortical locations and lesions of a different nature. However, we found that gelastic seizures with smiling were a more homogenous group with regard to location in the temporal lobe, which we aimed to show by evaluating the patients included in this study.
Keywords: Epilepsies, Partial; Seizures; Crying